2003
DOI: 10.1016/s0042-6989(03)00008-7
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the GABAergic system in the action of 2-amino-4-phosphonobutyrate on the OFF responses of frog retinal ganglion cells

Abstract: Perfusion of dark adapted frog eyecups with the ON pathway blocker 2-amino-4-phosphonobutyrate (APB) not only abolished the ganglion cells (GCs)' ON responses and the ERG b-wave, but it markedly potentiated the OFF responses of all ON-OFF and phasic OFF GCs and the d-wave amplitude of a simultaneously recorded ERG as well. The blockade of GABA(A) and GABA(C) receptors by picrotoxin eliminated this potentiating effect in 24 out of 41 GCs, although in the rest of the cells it did not produce any change in the AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…For this reason, well known GABAa and GABAc receptors antagonist, picrotoxin, was used in the current investigations. Previous reports (Popova et al, 2003;Kupenova et al, 2008) as well as the results of the current study show that picrotoxin enhances ERG b-wave but has no remarkable effects on ERG sensitivity as shown in Table 1. When GABA receptors were blocked with picrotoxin, Rubus coreanus treatment still increased ERG b-wave and significantly affected the ERG sensitivity (Fig.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…For this reason, well known GABAa and GABAc receptors antagonist, picrotoxin, was used in the current investigations. Previous reports (Popova et al, 2003;Kupenova et al, 2008) as well as the results of the current study show that picrotoxin enhances ERG b-wave but has no remarkable effects on ERG sensitivity as shown in Table 1. When GABA receptors were blocked with picrotoxin, Rubus coreanus treatment still increased ERG b-wave and significantly affected the ERG sensitivity (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies show that when eyecups preparation is treated with GABA receptors antagonist, it results in an increase in ERG b-wave and other parts of ERG (Popova et al, 2003;Kupenova et al, 2008). Therefore, it is possible that the improvements caused by Rubus coreanus in the current study are due to its antagonistic activity on GABA receptors.…”
Section: Discussionmentioning
confidence: 68%
“…In the present study, a known antagonist of GABAa and GABAc (picrotoxin) was used to inhibit GABA receptors in the retina. The present study and previous investigations showed that picrotoxin increases ERG b-wave amplitude [19,30]. It was also found that picrotoxin did not significantly improve ERG sensitivity (Table 2).…”
Section: Discussionsupporting
confidence: 63%
“…Previously, our group and others reported that GABA receptor antagonists amplify ERG waves, particularly the b-wave, in eyecup preparations [16,19,30]. Increased ERG b-wave amplitude may be affected by the GABA antagonistic properties of P. vittata.…”
Section: Discussionmentioning
confidence: 83%
“…These results appear to be inconsistent with the present data because the efficacy of L -AP4 is similar on mGluR4, mGluR6, and mGluR8 in pharmacological assays on transfected cells (EC 50 = 0.32, 0.055, and 0.06 μM for mGluR4, 6, and 8, respectively, Thomas et al, 2001), and therefore application of L -AP4 is expected to suppress the Off-responses through activation of the mGluR8 receptors. How then is the Off-response preserved, and in some cell types even potentiated (Popova et al, 2003), when both mGluR6 and mGluR8 are activated by L -AP4? One possibility is that activation of mGluR6 receptors suppresses signaling through the On-pathway, and thus reduces the excitatory drive to amacrine cells that provide cross-over inhibition from the On to the Off-sublaminae of the IPL (Wässle et al, 1986; Cohen, 1998; Zaghloul et al, 2003; Manookin et al, 2008).…”
Section: Discussionmentioning
confidence: 99%